Conformation and processing of cathepsin D. Issue 10 (October 1985) - Pain, Roger H.; Lan, Tamara; Turk, Vito
Abstract : Cathepsin D occurs in two forms, a single polypeptide chain (Mr 44000) and a non-covalent complex of two peptides of Mr 14000 and 30000 that is derived by proteolytic processing of the 44000 polypeptide. The two forms from bovine spleen are closely similar in secondary structure content, in aromatic amino acid environment and in the two step denaturation behaviour. Enzyme activity is lost irreversibly on denaturation but conformation can be partially regained. The two separated chains will only refold partially and this is related to their positions in the overall structure of cathepsin D. It is suggested that the processing step is related to protein turnover.